The Meaning of Building Orientation at Taneyan Lanjhang in Madura - Erik Yuliar Ramadhan; RA Retno Hastijanti (International Conference of Innovation and Community Engagement, 2024)
The understanding of the meaning of building orientation between traditional society and modern society has a very striking difference. Climatological considerations by modern society are not always correct when used to examine the meaning of building orientation by traditional society. The expression of the facing direction of the Madura traditional house building or commonly called Taneyan Lanjhang, is one example of a cultural result that is based more on the meaning underlying the thinking patterns of the community, it is strongly influenced by the existence and way of life of the community. Another factor that is also very instrumental in the orientation of Taneyan Lanjhang is the condition of the Madura Government since the 15th century, the beginning of the entry of Islam, not only affects the change of behavior and culture of the Madurese people, but also affects the Orientation of the Taneyan Lanjhang House Arrangement which is facing towards the Qibla (West). By using a phenomenological approach to the community and figures, it is hoped that it can emphasize the true "meaning of the orientation of the Taneyan Lanjhang Building". Because the meaning of the orientation of this building is not only based on religious and visual influences, but is based more on the deepest essence of what exists in the minds of the people. Therefore, the existence of Taneyan Lanjheng to this day is a reflection of the basic values of the identity of its people